Causative-Based Integral Policy As A Response To Criminogenic Factors In The Distribution Of Subsidized Fuel - Muhammad Abdul Azis; Siti Fadila Nuramelia; Muhammad Thufail Ariiq; Alya Synthia Kurniawati; Riski Ananda Kusuma Putri; Misshouw Meilany Putri; Dafirly Salsadilla Dosanto (Punggawa Legacy Center, 2026)
This study examines how non-adaptive oil and gas regulations function as criminogenic factors in the distribution of subsidized fuel and formulates an integral policy recommendation to address the misuse of subsidized fuel. This research uses a normative juridical approach with doctrinal legal research. Legal materials were collected through library research and analyzed qualitatively within a normative framework. The findings show that the misuse of subsidized fuel is not solely caused by individual wrongdoing, but is also triggered by the mismatch between regulation, socio-economic conditions, and public access to energy. This disharmony creates criminogenic conditions that encourage various forms of distributional deviation. Effective countermeasures require a combination of penal, non-penal, and social policy approaches.